2014
DOI: 10.4236/ojms.2014.44029
|View full text |Cite
|
Sign up to set email alerts
|

Mollusks of the Rocky Intertidal Zone at Three Sites in Oaxaca, Mexico

Abstract: The community of mollusks at three rocky intertidal zone in Oaxaca, Mexico was analyzed. Two samplings per site were conducted. At each sampling the inspected area was 10 m 2 . The sampling unit was 1 m 2 . 5862 specimens were examined. 68 mollusks species were identified. The families better represented in species richness were: FISSURELLIDAE, MURICIDAE, LOTIIDAE, MYTILIDAE, CHAMIDAE, ISCHNOCHITONIDAE y CHITONIDAE. The species that had the greatest density were Lottia discors, Siphonaria palmata, Lottia acuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
5
0
3
Order By: Relevance
“…Bivalvia was the least representative of the species richness; this may be due to the difficulty of collecting bivalves in the rocky subtidal zone (Muñiz-Sánchez, 2015), while in most studies of the Gulf of California and the Mexican Pacific it is the class with the second greatest diversity within the mollusk community. On the other hand, Landa-Jaime et al (2013) and Flores-Rodríguez et al (2014) also reported a greater diversity of polyplacophorans.…”
Section: Discussionmentioning
confidence: 94%
“…Bivalvia was the least representative of the species richness; this may be due to the difficulty of collecting bivalves in the rocky subtidal zone (Muñiz-Sánchez, 2015), while in most studies of the Gulf of California and the Mexican Pacific it is the class with the second greatest diversity within the mollusk community. On the other hand, Landa-Jaime et al (2013) and Flores-Rodríguez et al (2014) also reported a greater diversity of polyplacophorans.…”
Section: Discussionmentioning
confidence: 94%
“…Brachidontes puntarenensis 74 México: Golfo de California, Sonora (Puerto Peñasco); Costa Rica: Puntarenas, Golfo de Nicoya; Ecuador: Isla Galapagos y Perú: Yasila (Piura) (Keen, 1971;Coan & Valentich-Scott, 2012;Galeana-Rebolledo et al, 2012;Torreblanca-Ramírez et al, 2012; Acar pusilla 72 México: Guerrero (Isla la Roqueta y Acapulco) y Chile (Villalpando, 1986;Galeana-Rebolledo et al, 2012;Flores-Garza et al, 2014 Skoglund, 2001;Flores-Rodríguez et al, 2003;Valdés-González et al, 2004;Flores-Rodríguez et al, 2007;Ortiz-Arellano & Flores-Campaña (2008); Coan & Valentich-Scott, 2012;Esqueda-González et al, 2014;Flores-Garza et al, 2014;Flores-Rodríguez et al, 2014 (Skoglund, 2001;Valdés-González et al, 2004;Barba-Marino et al, 2010;Coan & Valentich-Scott, 2012;Flores-Rodríguez et al, 2012;Esqueda-González et al, 2014;Flores-Garza et al, 2014;Galeana-Rebolledo et al, 2012;DL y WMSDB) Las Gatas…”
Section: Especie N Distribución Conocida Nueva Distribuciónunclassified
“…De la literatura sobre la Subclase Opisthobranchia para el Pacífico Americano, la mayor cantidad de reportes analizan aspectos con enfoque en taxonomía y sistemática (Millen & Gosliner 1985, Bertsch 1995, Wagele & Willan 2000, Hermosillo & Valdés 2004, Valdés 2004, Valdés & AnguloCampillo 2004, Millen 2006, Hermosillo & Valdés 2007aMillen & Hermosillo 2007, Camacho-García & Gosliner 2008Hermosillo & Valdés 2008, Zamora & Naranjo 2008, Behrens et al 2009, Carmona et al 2014, Pola et al 2014, Goddard & Valdés 2015, Shipman & Gosliner 2015, también con listados de especies (Bertsh et al 1972, Angulo-Campillo 2000, Montoya et al 2001 1 , Hermosillo 2004, Hermosillo & Brehens 2005, Hermosillo & Camacho-García 2006, Nakamura 2007, Bertsch 2008Hermosillo & Gosliner 2008, Castillo 2010, Flores-Rodríguez et al 2014, otros enfoques son los biogeográficos (Gosliner 1991, Barraza 2009, Hermosillo 2003, Bertsch 2009), reproducción y desarrollo (Goddard 2005, Ávila-Poveda et al 2014, defensa química (Guido & Ghiselin 1998, Cimino & Ghiselin 1999, Ginsburg & Paul 2001, y aspectos ecológicos (Nybakken 1978…”
Section: Introductionunclassified